Fund Support for Debt- and Debt-Service-Reduction Operations. (Policy Papers; Policy Paper, 2021)
The note concludes that the Fund could support a member's use of buybacks, cash sweeteners, or collateral in the context of a Fund-supported program, provided that (i) debt restructurings using buybacks, cash sweeteners or collateral offer significant efficiency gains relative to debt restructurings that do not rely on such instruments, but are underpinned by a regular Fund-supported program; and (ii) an adequate cushion of non-multilateral debt remains after the operation. The conditions under which buybacks, cash sweeteners or collateral can be expected to deliver significant efficiency gains are narrow and specified in some detail.